2015
DOI: 10.1097/cco.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle control as a promising target in melanoma

Abstract: http://links.lww.com/COON/A12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 39 publications
3
50
0
3
Order By: Relevance
“…The addition of a third drug might help to overcome resistance and several trials are ongoing testing the triple combination of MEK plus BRAF inhibitors with MET, (46,47). It has been demonstrated that in resistant melanoma cell lines harboring BRAF splicing forms or BRAF amplifications stopping BRAF inhibition, leads to melanoma regression (48,49).…”
Section: Strategies To Overcome Resistancementioning
confidence: 99%
“…The addition of a third drug might help to overcome resistance and several trials are ongoing testing the triple combination of MEK plus BRAF inhibitors with MET, (46,47). It has been demonstrated that in resistant melanoma cell lines harboring BRAF splicing forms or BRAF amplifications stopping BRAF inhibition, leads to melanoma regression (48,49).…”
Section: Strategies To Overcome Resistancementioning
confidence: 99%
“…2,3,25 The results of our synergy studies using matched vemurafenib-sensitive and vemurafenib-resistant A375 and K4 cell lines are particularly intriguing and support the therapeutic strategy of combining CDK inhibitors with targeted MAPK therapies. To explain the mechanism of this synergy would be highly speculative, however, further exploration of the physiologic mechanisms responsible for the synergy of these drug combinations is needed to elucidate and fine-tune their potential therapeutic benefits.…”
Section: Ink4amentioning
confidence: 93%
“…2 Alterations in this pathway that lead to amplified CDK4 pathway signaling and aberrant cell proliferation have been clinically correlated to increased melanoma risk. Patients harboring germline homozygous deletions and loss-offunction (LOF) mutations in CDKN2A (the gene encoding the p16 INK4A protein) and activating mutations in CDK4 are 50 times more likely to develop melanoma.…”
Section: Ink4amentioning
confidence: 99%
See 1 more Smart Citation
“…113 A number of alterations concerning the p16 INK4A :cyclin D-CDK4/6:RB pathway have been reported in melanoma. 7,114 Several different orally bioavailable, specific small molecule inhibitors of CDK 4 and 6 are currently available. By targeting CDK4/6, they inhibit phosphorylation of retinoblastoma protein and thus prevent CDK-mediated G1-S phase transition.…”
Section: Perspectivementioning
confidence: 99%